Teaching Religious Tolerance Through Critical and Evaluative Reading Course for English Language Education Students - Ana Wiyasa Nugrahawati (ELE Reviews: English Language Education Reviews, 2023)
Religious tolerance is crucial for bridging a good intercultural interaction among people from different religious backgrounds. In the context of teaching, the critical and evaluative reading course is one of the courses that can facilitate students to foster their religious tolerance. This research aims to investigate the implementation of critical and evaluative reading course in building students’ religious tolerance. Taking the case at UIN Raden Mas Said, this descriptive research collected the data through interviews, observation, and document analysis. The findings showed that the fundamental aspects for practicing reading comprehension in critical and evaluative reading course are multimodal text materials addressing religious, cultural, and value practices and beliefs taken from various media, printed or online. The teaching strategy was reading to learn to help students build critical thinking. The students were able to perform religious tolerance understanding during the study period. It implies religious tolerance can be cultivated through reading courses using multimodal texts that can help students in their daily intercultural interaction practices.